Leptin receptor expression during the progression of endometrial carcinoma is correlated with estrogen and progesterone receptors - Méndez López, Luis Fernando; Zavala Pompa, Ángel; Cortés Gutiérrez, Elva Irene; Cerda Flores, Ricardo Martín; Dávila Rodríguez, Martha Imelda (2015)
Abstract Introduction: The hormone leptin, which is produced in the adipose tissue, may influence tumorigenesis directly via its receptor (Ob-R). Thus, a role for Ob-R in endometrial carcinogenesis has been proposed. However, most studies neither included samples of the entire histological progression of endometrial carcinoma nor examined Ob-R jointly with the estrogen and progesterone receptors (ER and PR, respectively). Material and methods: To determine the fluctuations of Ob-R, ER, and PR during the histological progression of endometrial carcinoma, we assessed their expression via immunohistochemistry (IHC) in six histological types of endometrium (proliferative, secretory, nonatypical and atypical hyperplasia, and endometrioid and nonendometrioid endometrial carcinoma), in which we performed histopathological and digital scoring for the quantification of receptors. Results: We found that Ob-R expression was positively correlated with that of ER and PR (r = 1, p < 0.001; r = 0.943, p < 0.005, respectively), and there was a significant difference in Ob-R expression among proliferative normal endometrium, hyperplasias, and carcinomas, according to their relative digitally scored Ob-R expression (p < 0.001). In addition, we observed that Ob-R expression in the secretory endometrium was more similar to that of carcinomas than to its proliferative counterpart. Conclusions: These results indicate that Ob-R expression fluctuates during endometrial carcinogenesis in correlation with ER and PR, suggesting that Ob-R expression in vivo is highly dependent on estrogen and progesterone activities in the endometrium and on its ER and PR status, as suggested previously by in vitro studies. Key words: Ob-R, endometrial carcinoma, immunohistochemistry